2014
DOI: 10.1111/cen.12601
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aerobic exercise training on serum osteocalcin, adipocytokines and insulin resistance on obese young males

Abstract: In a physiological axis of bone-fat-energy metabolism, exercise-induced body fat reduction and improved insulin sensitivity were accompanied by an increase in serum osteocalcin and leptin levels, but other factors also seem to be involved in this interrelationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 34 publications
2
57
2
1
Order By: Relevance
“…Our results are consistent with findings of Kim et al. (), Dieli‐Conwright et al. () and Levinger et al.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with findings of Kim et al. (), Dieli‐Conwright et al. () and Levinger et al.…”
Section: Discussionsupporting
confidence: 94%
“…A study in obese individuals has shown that the levels of serum carboxylated OC and insulin sensitivity are significantly improved after acute exercise compared to their levels at rest-control sessions [52]. Similarly, in another study, the content of serum OC increased significantly after 8 weeks of aerobic training, which gives a possibility that chronic exercise might also have a certain effect on OC [58]. On the contrary, it has been shown that 6-month chronic exercise in obese older adults did not have a significant impact on serum UcOC [60].…”
Section: Oc and Exercisementioning
confidence: 95%
“…It is important to note that OC concentration was significantly decreased in patients with T2DM and metabolic syndrome [58,59], implying that OC may have a positive regulation function on glucose and lipid metabolisms. A study in obese individuals has shown that the levels of serum carboxylated OC and insulin sensitivity are significantly improved after acute exercise compared to their levels at rest-control sessions [52].…”
Section: Oc and Exercisementioning
confidence: 99%
“…Exercise improved insulin sensitivity and reduced bone loss in Otsuka Long-Evans Tokushima Fatty Rats (77). Both acute bouts of exercise and long-term training improved insulin sensitivity and increased serum OC in obese men (78,79). Improved insulin sensitivity with exercise is associated with a change in OC (80).…”
Section: Exercisementioning
confidence: 99%